Bridging the Archipelago: Toward an Integrative Approach to Studying Bureaucratic Politicization - Belloir A; Shaw R; Van den Berg C (International Public Policy Association, 2025)
Despite ample attention to bureaucratic politicization in the public administration literature, most research remains siloed, focusing on individual forms of politicization (formal, functional, or administrative) and limited to single-country analyses. When a comparative stance is adopted, it often concentrates on comparing countries with the same administrative tradition (e.g., Westminster countries). This paper advocates for a comprehensive comparative research approach that integrates all forms and spans administrative traditions, treating the three forms of politicization as analytically distinct but empirically interdependent. Drawing on semi-structured interviews with senior civil servants (n=27) in four countries with distinct administrative tradition - Ireland (Westminster), the Netherlands (Germanic), Norway (Scandinavian), and Spain (Napoleonic) – the study introduces an integrated typology and applies it to demonstrate how politicization manifests across various administrative contexts. The findings reveal that politicization is best understood as a composite phenomenon shaped by institutional rules, organizational practices, and civil servants’ interpretive behaviors. This study provides a cross-dimensional, comparative lens that not only bridges conceptual silos, but also offers a more nuanced, context-sensitive understanding of how politicization unfolds in practice.
Keywords: bureaucratic politicization; civil service; administrative traditions; political-administrative relations; bureaucracy